‘Survival-driven’ or ‘policy-driven’—research on the motivation and economic consequences of the mixed-ownership reform of state-owned enterprises - Xiuting Wang (PLoS ONE, 2026)
Mixed-ownership reform (MOR) represents a pivotal policy instrument for revitalizing China’s state-owned enterprises (SOEs); however, its outcomes exhibit substantial heterogeneity. This variation implies that the intrinsic motivations behind reform—whether prompted by regulatory compliance or economic necessity—may constitute an understudied determinant of its efficacy. This research empirically examines how reform motivations influence the economic outcomes of mixed-ownership restructuring. Utilizing panel data from Chinese listed SOEs between 2013 and 2022 and employing a double fixed-effects model, we analyze the interaction between reform attributes—namely, breadth (ownership diversity) and depth (proportion of nonstate ownership)—and reform motivations, classified according to prereform profitability. Our results indicate that in SOEs characterized by survival-driven motives, deeper reform significantly improves firm performance. Nonetheless, this positive relationship is moderated by regional marketization levels. Conversely, reforms motivated primarily by policy directives demonstrate weaker effects on performance. These findings underscore that the impacts of mixed-ownership reform are not monolithic but are fundamentally conditioned on initial motivations and external institutional contexts. This study contributes to a refined theoretical framework for interpreting the heterogeneous effects of SOE reform and offers actionable implications for formulating context-sensitive policies.